Primary Retropharyngeal Synovial Sarcoma - Shi, H. (AJNR Am J Neuroradiol, 2009)
SUMMARY: Synovial sarcoma is the third most common histologic type of extremity soft tissue sarcoma. However, primary retropharyngeal synovial sarcoma is extremely rare. We present a case of primary retropharyngeal synovial sarcoma in a 60-year-old woman. The radiographic imaging of our present cases was characteristic of a heterogeneously enhancing mass.